Family involvement and dividend policy in closely held firms (2014)
This article examines the effects of family involvement on dividend policy in closely held firms that face agency problems involving majority?minority shareholders. We argue that minority shareholders press for dividends when they perceive situations fostering wealth expropriation. Looking at 458 Colombian companies, we find that family involvement in management does not affect dividend policy; family involvement in both ownership and control through pyramids affects dividend policy negatively; and family involvement in control through disproportionate board representation affects dividend policy positively. Thus, family influence on agency problems, and hence on dividend policy as a mitigating mechanism, varies depending on family involvement.